Diseño de un dosificador de jugo en la industria los helados de Salcedo Corpicecream S. A. para el aumento de productividad en el área de dosificación y congelación - Choloquinga Chanaluisa, Manuel Cruz (2023)
The purpose of this research project is to design a juice dispenser for the industry Los Helados de Salcedo CROPICECREAM S.A, referring to the analysis of the problems encountered in the area of dosing and freezing. With the implementation of the prototype, juice waste is avoided, manual dosing is streamlined and dosing times are reduced. The concurrent design methodology of Carles Riva Romeva has been applied, which consists of four levels of definition for the design of a prototype, which are: Product definition, conceptual design, materialization design and detail design. With the application of this methodology, it is possible to design a prototype that solves the problems evidenced in the aforementioned area.